Steganografi Pada Digital Image Menggunakan Metode Least Significant Bit Insertion - Siti Nur’aini (Universitas Islam Negeri Walisongo Semarang, 2019)
Steganography is a way to hide messages or confidential data in a medium called a carrier file. Embedding is done by the Least Significant Bit Insertion method, which is to replace the lowest bit of Red Green Blue (RGB) each pixel with the data bit you want to insert. With this method the difference between pixels that have not been pasted by messages and pixels that have been pasted by messages cannot be distinguished by human eye sight. Because the LSB insertion method is used, it is necessary to consider the type of digital image format used, this is necessary to avoid the loss of messages when extracting. And the best digital image format used is the 24-bit BMP because the BMP format is lossless compression